Treatment of severe aplastic anemia with a combination of horse antithymocyte globulin and cyclosporine, with or without sirolimus: a prospective randomized study - Scheinberg, Phillip (Ferrata Storti Foundation, 2009)
BACKGROUND: We hypothesized that the addition of sirolimus to standard horse antithymocyte globulin (h-ATG) and cyclosporine (CsA) would improve response rates in severe aplastic anemia, due to its complementary and synergistic properties to cyclosporine A. DESIGN AND METHODS: To test this hypothesis, we conducted a prospective randomized study comparing hATG/CsA/sirolimus to standard h-ATG/CsA. A total of 77 patients were treated from June 2003 to November 2005; 35 received h-ATG/CsA/sirolimus and 42 h-ATG/CsA. The two groups were well matched demographically and in blood counts prior to therapy. The primary end-point was hematologic response rate at 3 months, defined as no longer meeting the criteria for severe aplastic anemia. The study was powered to show a superior hematologic response rate of h-ATG/CsA/sirolimus compared to standard h-ATG/CsA. RESULTS: The overall response rate at 3 months was 37% for h-ATG/CsA/sirolimus and 50% for h-ATG/CsA and at 6 months 51% for h-ATG/CsA/sirolimus and 62% for h-ATG/CsA. After a planned interim analysis of 30 evaluable patients in each arm, accrual to the h-ATG/CsA/sirolimus arm was closed, as the conditional power for rejecting the null hypothesis was less than 1%. The rate of relapse, clonal evolution, and survival (secondary outcomes) did not differ significantly between patients treated with the two different regimens. CONCLUSIONS: Despite a theoretical rationale for its use, sirolimus did not improve the response rate in patients with severe aplastic anemia when compared to standard h-ATG/CsA